PENERAPAN MODEL PEMBELAJARAN MULTIDIMENSIONAL PADA PEMBELAJARAN FISIKA POKOK BAHASAN TEKANAN DALAM RANGKA MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA DI SMP NEGERI 1 WEDARIJAKSA KABUPATEN PATI (UPEJ Unnes Physics Education Journal, 2023)
This study aims to (1) determine the implementation of multidimensional learning models; (2) determine the improvement of students' science process skills by applying ultidimensional learning models; (3) Knowing students' responses to the implementation of the multidimensional learning model. The science process skills assessed are basic skills, namely: hypothesizing, interpreting data, applying concepts, and communication. The results of observations on the implementation test of the multidimensional learning model for 3 consecutive meetings were carried out very well with the average score from meetings 1 to 3 of 3.8; 3.7 and 3.65 from the highest score 4. There was an increase in students' science process skills after the application of the multidimensional learning model with a gain value of 0.7 included in the criteria for high improvement. Student responses to the application of the multidimensional learning model are high with an average student response percentage of 78.05% including in the high category.